COMPOSTING OF ANIMAL MANURE - Tosun, Ceren; Binici, M. Sinan; Mehmetli, Ebru; Baban, Ahmet; Manav, Neslihan; Coskun, Tamer; Debik, Eyup (YILDIZ TECHNICAL UNIV, 2011)
In this study, the composting capacity of animal manure has been evaluated to increase the usage capacity of the animal manure within the frame of healthy environment, and to increase economical and social benefits in selected pilot areas by following a sustainable method. Therefore, the effect of four different animal manure: straw: bulking agent (polyethylene) ratios (% 50:% 50, % 25:% 75, % 47.5:% 47.5:% 5, % 45: % 45:% 10) in compost efficiency has been investigated for 92 days. The amount of oxygen has been provided more than 5% in the reactors. The difference in temperatures in four reactors has been observed depending on the moisture content and C/N ratio. The temperature has increased in the first five days due to the microbial activity and after 27thday the temperature has reached to a stable value. The C/N ratio of the mixtures has decreased 50% at the end of the stabilization period. The moisture content has not changed dramatically. The organic matter content has decreased from 85% to 55%. It was observed that the bulking agent, which is used to provide homogen oxygen distribution in the system, has not been useful for the animal manure efficiency. Temperature, oxygen, moisture content, volatile solid matter, pH, C/N ratio, heavy metal ratio, E. Coli and Salmonella have been investigated in the compost during the composting process. The composting which was processed by using 50%: 50% manure: straw ratio has resulted in the better compost quality.
Keywords: Animal manure; straw; compost; C/N ratio; Engineering